Training on Optimizing the Use of Microsoft Word Applications for Students of the Faculty of Fisheries, University Abulyatama - Lia Handayani; Nurhayati; Agus Naufal; Faisal Syahputra; Azwar Thaib; Suraiya Nazlia; Ainal Mardiah (Fakultas Pertanian, Universitas Samudra, 2023)
The rapid development of technology directly requires users to able adaptation to these developments. Likewise, students must be able to adapt to technology so that activities related to lectures can be done easily. This service activity aims to help students understand the use of Microsoft word application software so that it can make it easier for them to do assignments, write reports, write final assignment and other needs. The method used in this service activity in the preparation, implementation and evaluation of activities. The training materials include how to write papers, paragraphs, insert tables and merge cells, insert images, page setup, create a list of images and create a table of contents. Based on the results of the evaluation of this service activity, it was found that this activity had a positive impact on participants. This is indicated by the increase in the the ability of participants who participate in the activity. In addition, the participants were very enthusiastic about participating in this activity until it was finished.